New integrated weaning indices from mechanical ventilation: A derivation-validation observational multicenter study - Vahedian-Azimi, Amir; Gohari-Moghadam, Keivan; Rahimi-Bashar, Farshid; Samim, Abbas; Khoshfetrat, Masoum; Mohammadi, Seyyede Momeneh; de Souza, Leonardo Cordeiro; Mahmoodpoor, Ata (Frontiers in Medicine, 2022)
Background: To develop ten new integrated weaning indices that can predict the weaning outcome better than the traditional indices. Methods: This retrospective-prospective derivation-validation observational multicenter clinical trial (Clinical Trial.Gov, NCT 01779297), was conducted on 1,175 adult patients admitted at 9 academic affiliated intensive care units (ICUs; 4 surgical and 5 medical), from Jan 2013 to Dec 2018. All patients, intubated and mechanically ventilated for at least 24 hours and ready for weaning were enrolled. The study had two phases: at first, the threshold values of each index that best discriminate between a successful and an unsuccessful weaning outcome was determined among 208 patients in the derivation group. In the second phase, the predictive performance of these values was prospectively tested in 967 patients in the validation group. In the prospective-validation set we used Bayes’ theorem to assess the probability of each test in predicting weaning. Results: In the prospective validation group, sensitivity, specificity, diagnostic accuracy, positive and negative predictive values, and finally area under the receiver operator characteristic curves and standard errors for each index (ten formulae) were calculated. Statistical values of ten formulae for aforesaid variables were higher than 87% (0.87 to 0.99). Conclusions: The new indices can be used for hospitalized patients in intensive care settings for accurate prediction of the weaning outcome.